Successful self-publishing: how to self-publish and market your book (Books for Writers, ,, 2019)
"Do you want to successfully self-publish? There are thousands of new books being published every day, but many self-published books quickly sink to the bottom of the pile. Many authors are frustrated because there are so many options for self-publishing, and they don't know which one to choose or what will be best for their book. Others spend thousands of dollars to publish and end up broken-hearted with the result. But it doesn't have to be this way. I've spent the last seven years self-publishing bestselling fiction and non-fiction books and in 2011, I left my day job to become a full-time author entrepreneur. I've made lots of mistakes along the way, but through the process of self-publishing 17 books, I've learned the most effective way to publish and market your books." --

How to Make a Living with your writing: Turn Your Words into Multiple Streams of Income (Books for Writers, ,, 2021)
Do you want to make a living with your writing? Do you want to turn your words into multiple streams of income? I’m Joanna Penn and I left my job as a corporate cubicle slave a decade ago to become a full-time author entrepreneur. In this completely updated Third Edition, I’ll explain how I make a living with my writing and share tips from other writers on how you can do it too with practical, actionable advice that you can implement for yourself. If you love to create and you’re ready to learn fresh skills in a fast-changing environment, this book will give you lots of ideas on how to make money with your words. Each chapter provides ideas you can use to research each opportunity in more detail and questions to guide your thought process. Sometimes it’s just about knowing what’s out there in order to find what’s right for you.